Marketing and Service Strategy in an Effort to Improve the Quality of Competition at the Hajj and Umrah Travel Agency at PT. Qiblatain Ama Tour - Ahya Khoirunisa Acwa (Demagogi: Journal of Social Sciences, Economics and Education, 2026)
Increasing competition in the Hajj and Umrah travel agency industry requires companies to implement effective marketing strategies and service systems to enhance competitiveness. This study aims to analyze the marketing strategies, service systems, and factors influencing the competitiveness of PT. Qiblatain Ama Tour in Semarang City. This research employs a qualitative method with a descriptive approach through observation, interviews, and documentation involving managers, employees, and pilgrims. Data analysis was conducted through data reduction, data presentation, and conclusion drawing, with data validity ensured through source triangulation. The results show that marketing strategies include the implementation of the marketing mix, utilization of digital media, and strengthening of branch networks. The service system focuses on excellent service, intensive pilgrim assistance, information transparency, and improvement of human resource quality. Key factors influencing competitiveness include service quality, pilgrims’ trust, employee professionalism, and compliance with government regulations.